Pembelajaran PAI Berbasis Digital Spiritual Well-Being untuk Mengurangi Kecemasan Akademik Siswa Sekolah Dasar - Azmi Yudha Zulfikar (Yayasan Madinah Al-Aziziyah, 2026)
The development of digital technology has transformed Islamic Religious Education learning, particularly in material delivery, interactive media use, and students’ access to learning resources. However, the use of technology in Islamic Religious Education has predominantly focused on improving motivation, subject comprehension, and learning outcomes, while its role in supporting spiritual well-being and reducing academic anxiety among elementary school students remains insufficiently explored. This study aims to analyze the concept of digital spiritual well-being-based Islamic Religious Education and its potential to reduce academic anxiety among elementary school students. The study employed a library research method by reviewing books, scholarly articles, previous studies, and academic documents related to digital Islamic Religious Education, spiritual well-being, elementary student development, and academic anxiety. The data were analyzed through classification, reduction, interpretation, comparison, and synthesis of the selected literature. The findings indicate that academic anxiety may manifest as fear of examinations, concerns about grades, difficulty completing assignments, and low self-confidence during learning activities. Digital spiritual well-being-based Islamic Religious Education can be implemented through Islamic reflection videos, prayer and remembrance audio, interactive digital stories, gratitude journals, and reflective activities integrating patience, reliance on God, gratitude, and positive thinking. The study concludes that this approach has the potential to create a calming and meaningful learning environment while supporting students’ emotional readiness. This study contributes to the field by offering a conceptual framework that integrates digital technology, Islamic spiritual values, and academic anxiety management within elementary-level Islamic Religious Education.